2011
DOI: 10.1007/s12291-011-0154-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of DNA Extracted from Buccal Swabs for Microarray Based Genotyping

Abstract: Buccal cell usage has been shown by many to be a cost effective and safe method to isolate DNA for various biological experiments especially large epidemiological studies (Garcia-Closas et al. Cancer Epidemiol Biomarkers Prev 10:687-696, 2001). Non-invasive DNA collection methods are preferred over phlebotomy in order to increase study participation and compliance in research centers and for sick patients in hospital settings. There have been conflicting reports about the methodology and results obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Recently, a study also showed that saliva collected using the Oragene kit yielded high quantity and high quality DNA for genetic studies [ 17 ]. However, there are still concerns over using DNA extracted from saliva samples or buccal cyto-brushes for genotyping [ 18 , 19 ] due to possible bacterial contamination which may affect yield and quality of DNA [ 20 ]. Furthermore, there is lack of data on whether different biological samples can be used interchangeably for the genotyping of a specific gene of interest, especially for complex genes like the AMY1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study also showed that saliva collected using the Oragene kit yielded high quantity and high quality DNA for genetic studies [ 17 ]. However, there are still concerns over using DNA extracted from saliva samples or buccal cyto-brushes for genotyping [ 18 , 19 ] due to possible bacterial contamination which may affect yield and quality of DNA [ 20 ]. Furthermore, there is lack of data on whether different biological samples can be used interchangeably for the genotyping of a specific gene of interest, especially for complex genes like the AMY1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are available for collecting saliva for DNA, including “swish and spit,” saliva collection kits for DNA (e.g., Oragene ® , DNAgard ® , Norgen ® ), or swabs. The swish and spit method or Oragene ® kits are recommended as standard in EPHect, providing the best DNA quality and yield (51–53) . For general biomarker studies, the “passive drool” method for sample collection is preferred over other methods that stimulate saliva production (e.g., chewing on cotton), as the latter can alter hormone levels (50) .…”
Section: Resultsmentioning
confidence: 99%
“…Although buccal cells provides a smaller amount of DNA than blood, recently developed methods of genotyping use very small amounts of DNA (2-10 ng per assay) and thus allow the use of buccal cells as a source of DNA. Importantly, the use of non-invasive DNA collection methods has been shown to increase study participation rates [7].…”
Section: Introductionmentioning
confidence: 99%
“…DNA buccal swabs have been specifically designed to increase study participation and compliance in research centers and for sick patients in hospital settings. In fact, the cotton swab has long been a basic and essential tool for collecting DNA evidence for forensic casework analysis [7].…”
Section: Introductionmentioning
confidence: 99%